Analog Video in Moving Image Archives & Conservation: Infrastructures of Knowledge from Production to Preservation - Sorensen, Lauren (KULA)

(untitled) (University of Victoria Libraries, 2018)
The essay uses a set of theoretical ideas offered by Susan Leigh Star to argue for a shift in contemporary understandings of, and approaches to, video preservation. Instead of focusing on the granular characteristics of tape and their material stability, I argue, the audiovisual archival community should view preservation as a set of linked systems that function within a web of shifting perspectives and context-driven solutions.